PENENTUAN RUNUTAN Cu, Cr, Mn dan Fe DALAM MATRIKS AIR LAUT DENGAN SPEKTROFOTOMETRI SERAPAN ATOM DAN EKSTRAKSI PELARUT - Ardeniswan Ardeniswan; Sumardi Sumardi (Research Center for Chemistry - LIPI, 1993)
A method has been studied for the analysis of trace metals such as Cu, Cr, Mn, Fe in artificial seawater matrix samples using atomic absorption spectrophotometric (AAS). Concentration of theSe metals was carried out by extraction using methyl isobutyl ketone (MIBK) after being reacted with complexing agents, and transfered into aqueous solution by backextraction using 4 N nitric acid. The metal complexing agents used were ammonium pyrrolidinedithiocarbamate (APDC), sodium diethyldithlocarbamate (Na-DDC), mixture of equal ratio of APDC and Na-DDC. From these study it was found that use of APDC gave recovery for Cu, Cr, Mn and Fe 104.4; 25.4; 0; 83.0 % respectively at pH 5, while use of Na-DDC gave 83.5; 89.0; 79.4 and 81.3 % , respectively at the same pH. A mixture of equal ratio of APDC and Na-DDC was found to gave recovery for Cu, cr, Mn and Fe of 104.6; 103.9; 102.1 and 101.2 %, respectively at pH 5.